2020
DOI: 10.1177/0276236620909544
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Control in Lucid Dreams

Abstract: The objective of the present study is to explore lucid dream control strategies (LDCSs) facilitating the production of outcomes that are impossible in the real world. Participants are 107 adults who experienced at least one lucid dream per year. They completed an online survey including an open question on LDCSs. Responses were analyzed using a content analysis method with a consensus approach. The results revealed five categories of LDCSs used within the lucid dreams: verbal strategies, strategies based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Lucid participants had different strategies for reinstating the scene while dreaming (see also, Lemyre et al, 2020;Tholey, 1983). While some lucid participants were "just there" (sub-002), others used focused intention.…”
Section: Partial Scene Reinstatement Is Possible While Dreamingmentioning
confidence: 99%
See 2 more Smart Citations
“…Lucid participants had different strategies for reinstating the scene while dreaming (see also, Lemyre et al, 2020;Tholey, 1983). While some lucid participants were "just there" (sub-002), others used focused intention.…”
Section: Partial Scene Reinstatement Is Possible While Dreamingmentioning
confidence: 99%
“…Another survey study found that the majority of participants report having control only "frequently" (4 on a 6-point scale) in lucid dreams (Mota-Rolim et al, 2013). Further, there are differing aspects of dream control (Lemyre et al, 2020), such as whether the dream body or the environment of the dream are being manipulated with volition (Schredl et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online surveys of lucid dream experiences suggest there is large variation in how individuals pursue, experience, and utilize lucid dreams (Lemyre et al, 2020;Stumbrys, Erlacher, Johnson, et al, 2014). Being fully lucid and aware of the dream state implies that the dreamer can execute predetermined actions within the dream (Erlacher & Schredl, 2008), yet participants report often not being able to complete their intended actions due to "insufficient clarity" (Stumbrys, Erlacher, Johnson, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Online surveys of lucid dream experiences suggest there is large variation in how individuals pursue, experience, and utilize lucid dreams (Lemyre et al, 2020;. Being fully lucid and aware of the dream state implies that the dreamer can execute predetermined actions within the dream (Erlacher & Schredl, 2008), yet participants report often not being able to complete their intended actions due to "insufficient clarity" .…”
Section: Introductionmentioning
confidence: 99%